Comparison of intrinsic dynamics of cytochrome p450 proteins using normal mode analysis. (16th July 2015) - Dorner, Mariah E.; McMunn, Ryan D.; Bartholow, Thomas G.; Calhoon, Brecken E.; Conlon, Michelle R.; Dulli, Jessica M.; Fehling, Samuel C.; Fisher, Cody R.; Hodgson, Shane W.; Keenan, Shawn W.; Kruger, Alyssa N.; Mabin, Justin W.; et al.
Abstract Cytochrome P450 enzymes are hemeproteins that catalyze the monooxygenation of a wide‐range of structurally diverse substrates of endogenous and exogenous origin. These heme monooxygenases receive electrons from NADH/NADPH via electron transfer proteins. The cytochrome P450 enzymes, which constitute a diverse superfamily of more than 8, 700 proteins, share a common tertiary fold but < 25% sequence identity. Based on their electron transfer protein partner, cytochrome P450 proteins are classified into six broad classes. Traditional methods of pro are based on the canonical paradigm that attributes proteins' function to their three‐dimensional structure, which is determined by their primary structure that is the amino acid sequence. It is increasingly recognized that protein dynamics play an important role in molecular recognition and catalytic activity. As the mobility of a protein is an intrinsic property that is encrypted in its primary structure, we examined if different classes of cytochrome P450 enzymes display any unique patterns of intrinsic mobility. Normal mode analysis was performed to characterize the intrinsic dynamics of five classes of cytochrome P450 proteins. The present study revealed that cytochrome P450 enzymes share a strong dynamic similarity (root mean squared inner product > 55% and Bhattacharyya coefficient > 80%), despite the low sequence identity (< 25%) and sequence similarity (< 50%) across the cytochrome P450 superfamily. Noticeable differences in Cα atom fluctuations of structural elements responsible for substrate binding were noticed. These differences in residue fluctuations might be crucial for substrate selectivity in these enzymes.